Invasion Success of Bunias orientalis (Warty Cabbage) in Grasslands: A Mesocosm Experiment on the Role of Hydrological Stress and Disturbance - Corli, Anna; Walter, Julia; Sheppard, Christine S. (Frontiers in Ecology and Evolution, 2021)
Climate change is altering precipitation patterns, with higher frequency and magnitude of extreme events. Specifically, longer and more pronounced waterlogged conditions are predicted after rain spells as well as more frequent droughts, especially in Central Europe. Such hydrological changes can severely affect species performance and alter the function of ecosystems, as well as favor plant invasions. Competition with native communities may change depending on water stress. Bunias orientalis is an invasive plant that may benefit from disturbance or precipitation changes. We conducted a three-year mesocosm experiment in a common garden to investigate how invasion success of B. orientalis in native German grassland communities is affected by varying hydrological conditions (from very dry to waterlogged). We measured the establishment and growth of B. orientalis in varying water table depths in bare soil (simulating disturbance) versus in the community. Establishment and biomass of B. orientalis was generally highest under non-stress conditions. The species was also highly tolerant to dry conditions, but only when growing in bare soil. However, performance of B. orientalis was generally low, whereby interspecific competition in communities greatly limited invasion success. This might be due to the low competitive ability of the species in conditions of hydrological stress and the near-natural grassland communities with an extensive mowing regime used in our experiment. Our results suggest that invasion success of B. orientalis in grasslands will not increase if precipitation patterns change towards more extreme events. However, disturbance that creates bare soil patches might favour B. orientalis under drought conditions.